Perception of nursing workers humanization under intensive therapy - Azevedo Michelan, Vanessa Cecilia de [UNESP]; Spiri, Wilza Carla [UNESP] (Assoc Brasileira Enfermagem, 2018)
Objective: understand the perception of nursing workers working in the Intensive Care Unit (ICU) regarding humanization in the work environment. Method: we used the reference of phenomenology, structure of the phenomenon. Participated 25 nursing professionals working in an adult ICU of a university hospital, through focused interviews, answering the guiding question: What do you understand by humanization of the working conditions of the nursing team working in the ICU? Results: the analysis revealed the themes: humanization in the ICU; working condition in the ICU; management of people in the ICU and management process in the ICU. Final considerations: humanization is necessary through the change of the work environment and the managerial process, privileging the participatory management model as a way to transform theory into practice and value the worker.
Keywords: Humanization of Care; Intensive Care Unit; Health Personnel; Qualitative Research; Participative Management